Implementasi Mind Mapping Digital Dalam Transformasi Pembelajaran Pendidikan Agama Hindu Di Kelas XII SMA - Ni Wayan Gloriousintawaty, Ni Wayan Gloriousintawaty (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2025)
This research aims to improve student learning outcomes in Hindu Religious Education and Character, specifically the Tri Guna material, through the application of Digital Mind Mapping in class XII Semester I of SMA Negeri 6 Palangka Raya for the 2024/2025 academic year. The method used is Classroom Action Research (CAR) with the Kemmis & McTaggart model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research results show that the application of Digital Mind Mapping significantly improves student learning outcomes. The average score increased from 63.30 in the pre-cycle to 75.00 in the first cycle, and then further increased to 81.7 in the second cycle, with final mastery reaching 100%. Additionally, student activity in learning also increased, especially in discussions, problem-solving, and creativity in organizing concepts using Digital Mind Mapping. Digital Mind Mapping is proven to be an effective learning strategy for enhancing student understanding. Therefore, this method is recommended as an innovation in teaching Hindu Religious Education and Character